Design of Foodcourt Interior with The Theme of Omprog Gandrung with Postmodern Style in Banyuwangi - Nurhaliza, Sinatrya; Hapsari, Putri Sekar; Indarto, Indaro (Pendhapa, 2023)
Foodcourt Interior Design with the Theme Omprog Gandrung with a Postmodern Style in Banyuwangi Regency supports the needs of tourists as a manifestation of the development of the tourism sector in Banyuwangi Regency and aims to be a place that is able to facilitate user needs to become an attractive, comfortable and safe place with the theme Omprog Gandrung and applying a postmodern style. The design method used is the Pamuji Suptandar Design Method Program which consists of input, analysis/synthesis, and output stages. The approach used is function, ergonomics, aesthetics, and technical. The results of Foodcourt Interior Design with the Omprog Gandrung Theme with Postmodern Style in Banyuwangi Regency are foodcourt interior designs that have foodcourt stand facilities, dining areas, souvenir shops, music stages, talent rooms, sound control rooms, customer service, offices, front office & office waiting rooms.